Women in the legal profession in South Africa: traversing the tensions from the bar to the bench - Chitapi, Rudo Runako (Department of Public Law, 2015)
This paper takes the view that the substance of that knowledge and information is to be found with the very women we are concerned with. It seeks to investigate this by eliciting the experiences of women who have entered the profession, specifically the advocate’s profession, more commonly known as the Bar. Closer scrutiny of women in the profession in this way will determine whether and to what extent patriarchal normative attitudes still operative in the legal profession.